UV-Vis spectra and moisture content of retrofilled aged mineral oil with synthetic ester - Othman, N. A.; Zainuddin, H.; Yahaya, M. S.; Azis, N.; Ibrahim, Z.; Musni, M. A. C. (IEEE, 2023)
Retrofilling aged mineral oil (AMO) with ester oils is now being explored as an alternative option for the extension of transformer life. In transformer retrofilling, there is up to 10 % of aged mineral oil will be mixed with new oil. It is anticipated that the dielectric properties of the ester oil will be affected when the oils are mixed together. In this paper, synthetic ester (SE) oil was investigated in terms of its physicochemical properties after being mixed with various proportions of aged mineral oil. An accelerated thermal aging of mineral oil has been firstly prepared prior to the retrofilling with SE oil. The mineral oil was aged in a vacuum oven at 130 °C for 150 hours. There are three different proportions, i.e. 3 %, 5 % and 7 % were selected for use in the retrofilling process. Further, the retrofilled aged mineral-synthetic ester (AMO/SE) oil was tested for the moisture content and evaluation of degradation products through Ultraviolet-Visible Spectroscopy (UV-Vis) spectra. Based on the findings, it was interestingly found that the higher proportion of AMO has reduced the moisture content of retrofilled AMO/SE. In terms of UV-Vis spectra, the higher proportion of AMO has increased the absorbance with longer wavelength and it is in line with the concentration of dissolved decay products (DDPs). Overall, the moisture content and the concentration of DDPs of retrofilled AMO/SE has still meet the requirement as a new oil.